149 Advanced Cancer Care in the Community in Scotland: a national survey of General Practitioners. (14th March 2023) - Sinha, Shruti; Fenning, Stephen; Mills, Sarah; Porteous, Lorna; Bradshaw, Sineaid; Haldane, Nick; Bowden, Jo
Abstract : Background: Most people with deteriorating health prefer care that is home-based, providing sufficient support is available. Recent Scottish research has shown that people with advanced cancer are high users of acute care near the end of life, and at questionable value. The mainstay of advanced cancer care in the community is Primary Care. A large research study is underway examining care pathways, outcomes and experiences for people with advanced cancer in Scotland. The aim of our study was to explore GPs' perspectives of advanced cancer care in the community to inform the development of improved care pathways for patients and families. Methods: We undertook a national, online survey of GPs in Scotland via the platform Qualtrics. Question domains included communication from Oncology teams, enablers and barriers to community care and the current care offer in their practice. The survey was piloted with Regional Lead Cancer GPs, who later distributed the survey invitations regionally. Findings: 197 GPs completed the survey. 80% of respondents reported receiving written communication from Oncology about their patients' clinical management plans either 'always' (16%) or 'most of the time' (64%). Only 43% and 11% of respondents respectively reported a similar level of communication around patient understanding and anticipatory care planning. The presence or absence of adequate time was the most frequently identified enabler and barrier to delivering care. A large majority reported that their patients receive timely anticipatory care planning and clinical assessments from GPs. A wealth of constructive suggestions for improved care were provided. Conclusions: GPs are core providers of advanced cancer care in the community, but require adequate time and up to date information to do their job effectively. National Cancer and Palliative Care strategies and associated policies are under development by Scottish Government. Our findings will be shared with key stakeholders in this process.